1999
DOI: 10.1055/s-1999-8846
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiocirculatory Reactions after Concentric and Eccentric Exercise of the Shoulder

Abstract: Lower metabolic and cardiocirculatory reactions to eccentric compared to concentric exercise are known for large muscle groups. The extent of exercise reaction depends on the muscle mass involved and moreover differs between the various muscle groups, while it is unclear to which extent cardiovascular and metabolic reactions and differences between the types of work exist in the shoulder, also it is not known whether these reactions differ according to training status. Lactate production (LA), heart rate (HR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
2
7
1
1
Order By: Relevance
“…In addition, this mechanism could be responsible for the HR increase until 30 seconds of contraction 41 . Thus, the divergent results observed in the literature could be due to the difference between the contraction length, since Horstmann et al 2 and Mayer et al 3 evaluated the HR response during 1 minute of contraction, contrasting with the present study where the efforts was maintained for a mean of 12 seconds.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In addition, this mechanism could be responsible for the HR increase until 30 seconds of contraction 41 . Thus, the divergent results observed in the literature could be due to the difference between the contraction length, since Horstmann et al 2 and Mayer et al 3 evaluated the HR response during 1 minute of contraction, contrasting with the present study where the efforts was maintained for a mean of 12 seconds.…”
Section: Discussioncontrasting
confidence: 68%
“…The magnitude of HR response to isokinetic exercise is related to the intensity of the maximum tension, size of the mass of the contracting muscle group and time of muscular action. Since performed at the same intensity and for a long period of time, concentric contraction performed by young men produces greater HR elevation than eccentric contraction does 2,3,10,[25][26][27][28][29] . This characteristic is attributed to a low muscular metabolic demand required to perform the eccentric contraction, which has an important contribution from the passive tissues in torque generation 2,3 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few studies have investigated GH and testosterone responses to different muscle actions, and no studies have investigated responses to relatively loaded CON and ECC dynamic contractions. Since different muscle actions using the same muscle loading produce different metabolic and hormonal responses (Mayer et al 1999;Wideman et al 2002) and since previous data suggest that these differences may be from underloading of ECC muscle actions (Durand et al 2003), we investigated anabolic hormone responses to CON and ECC contractions using muscle loads relative to the respective CON and ECC 1-RMs in dynamic resistance exercise. We demonstrated that a resistance exercise regimen of CON or ECC muscle actions performed on weight stack machines at a percentage of the respective CON or ECC 1-RM produces similar GH, total testosterone, and free testosterone responses.…”
Section: Discussionmentioning
confidence: 99%
“…20 Eccentric exercise is benefi cial in evoking gains in muscle power and muscle spring stiffness, 21,22 increasing stiffness in the tendon, preventing injury to the muscletendon unit and the tendon itself, 21 and reducing pain associated with tendon disorders. 21,23,24 The advantages of eccentric exercise compared to concentric exercise are reduction of metabolic costs and O 2 consumption, 3,25 production of much greater force (i.e., two-to threefold) than that of concentric exercise, 26 and a better remodeling response. Ischemia and local hypoxia are thought to be major stimuli for VEGF-induced angiogenesis.…”
mentioning
confidence: 99%